2015
DOI: 10.1080/15384101.2015.1064565
|View full text |Cite
|
Sign up to set email alerts
|

Np9, a cellular protein of retroviral ancestry restricted to human, chimpanzee and gorilla, binds and regulates ubiquitin ligase MDM2

Abstract: Humans and primates are long-lived animals with long reproductive phases. One factor that appears to contribute to longevity and fertility in humans, as well as to cancer-free survival, is the transcription factor and tumor suppressor p53, controlled by its main negative regulator MDM2. However, p53 and MDM2 homologs are found throughout the metazoan kingdom from Trichoplacidae to Hominidae. Therefore the question arises, if p53/MDM2 contributes to the shaping of primate features, then through which mechanisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
25
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 64 publications
1
25
0
1
Order By: Relevance
“…HERV expression is very well-documented in testicular germ cell tumoursgerm cell tumour cell lines have been shown to express HK2 non-infectious particles [32] , [33] , [34] . HERV-K has also been shown to be overexpressed at specific stages of early embryonic development [7] , [9] , [11] , which we also observed using our novel method. Germ cell tumours also share with early embryonic cells similar traits of embryonic stem cell identity, such as the upregulation of the pluripotency factors Oct3/4, Nanog, and Sox2 [35] .…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…HERV expression is very well-documented in testicular germ cell tumoursgerm cell tumour cell lines have been shown to express HK2 non-infectious particles [32] , [33] , [34] . HERV-K has also been shown to be overexpressed at specific stages of early embryonic development [7] , [9] , [11] , which we also observed using our novel method. Germ cell tumours also share with early embryonic cells similar traits of embryonic stem cell identity, such as the upregulation of the pluripotency factors Oct3/4, Nanog, and Sox2 [35] .…”
Section: Discussionsupporting
confidence: 73%
“…The Np9-Rec-PLZF interaction results in the de-repression of the c-myc proto-oncogene, c-Myc overexpression, altered expression of genes regulated by c-Myc, and increased cell survival and proliferation [2] . Np9 protein is also reported to bind and regulate ubiquitin ligase MDM2, which represses the activity of p53 tumour suppressor [9] . Transcripts of np9 and rec are also found in human embryonic stem cells and human induced pluripotent stem cell lines, and are associated with maintenance of pluripotency [10] , [11] .…”
Section: Introductionmentioning
confidence: 99%
“…4E). We also observed an upregulation of the np9 and rec alternative transcripts, which encode for proteins with oncogenic potential and promoting expression of the IFITM1 antiviral factor (21)(22)(23)(24)(25). As well, KZFP-depleted iN were characterized by the upregulation of IFNγ and ISGs such as TNF, IFITMs, APOBEC3B, IRF1, IFIH1 (a.k.a.…”
mentioning
confidence: 76%
“…Previous studies have also shown that HK2 expression is high in specific stages of early embryonic development [6] , [12] , [13] , [17] . HK2 is upregulated in tumours with greater transcriptional similarity with testicular germ cell cancer, a type of malignancy known for a strong stem-cell identity.…”
Section: Discussionmentioning
confidence: 78%
“…In addition, Np9 protein is reported to bind and regulate ubiquitin ligase MDM2, resulting in the repression of p53 tumour suppressor [11] . Transcripts of np9 and rec are found in human embryonic stem cells and human induced pluripotent stem cell lines and are associated with maintenance of pluripotency [12] , [13] , and recently it has been demonstrated that the activation and silencing of a specific HERV-K LTR LTR5HS is associated with reciprocal up-and downregulation of hundreds of human genes, and can occur over long genomic distances [14] .…”
Section: Introductionmentioning
confidence: 99%